Comportamiento de la responsabilidad social de los trabajadores por cuenta propia, asociados a la actividad gastronómica de restaurantes en el Centro Histórico de Bayamo - Núñez Iza, Celina Rosario (2013)
The present diploma work was carried out in Bayamo, city belonging to the county of Granma, Cuba. The same one has as title “Behavior of the social responsibility of the self-employed workers associated to the gastronomic activity around historical center at Bayamo” and it has as objective to do a practical study of the main socially responsible practices for these small businesses. An exhaustive bibliographical revision was carried out and the historical- logical and inductive-deductive methods were used that facilitated the obtaining of necessary information for the elaboration of this work….